THE ROLE OF BIOLOGICALLY ACTIVE ADDITIVES IN MODERN MEDICINE - Narzullayeva Mehrangiz Azizkhonovna (PEDAGOGS, 2024)
Dietary supplements appeared 100 years ago. The world's first alfalfa food supplement was created by American chemist Carl Renborg. Today, the use of dietary supplements has become commonplace, and with the advent of the pandemic, the demand for them has increased tenfold. Vitamins and dietary supplements are taken for prevention, during various diseases, during recovery periods.